Pregnancy and birth planning during COVID-19: The effects of tele-education offered to pregnant women on prenatal distress and pregnancy-related anxiety - Derya, Yesim Aksoy; Altiparmak, Sumeyye; Akca, Emine; Gokbulut, Nilay; Yilmaz, Ayse Nur (Elsevier Sci Ltd, 2021)
Aim: This study aims to examine pregnancy and birth planning during COVID-19 and the effects of a tele-education offered to pregnant women for this planning process on prenatal distress and pregnancy-related anxiety. Method: The population of this quasi-experimental study was composed of pregnant women who applied for the antenatal education class of a public hospital in the east of Turkey during their past prenatal follow-ups and wrote their contact details in the registration book to participate in group trainings. The sample of the study consisted of a total of 96 pregnant women, including 48 in the experiment and 48 in the control groups, who were selected using power analysis and non-probability random sampling method. The data were collected between April 22 and May 13, 2020 using a Personal Information Form, the Revised Prenatal Distress Questionnaire (NuPDQ) and the Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). An individual tele-education (interactive education and consultancy provided by phone calls, text message and digital education booklet) was provided to the pregnant women in the experiment group for one week. No intervention was administered to those in the control group. The data were statistically analyzed using descriptive statistics (frequency, percentage, mean, standard deviation, min-max values) and t-test in dependent and independent groups. Results: The posttest NuPDQ total mean scores of pregnant women in the experiment and control groups were 8.75 +/- 5.10 and 11.50 +/- 4.91, respectively, whereby the difference between the groups was statistically significant (t=-2.689, p=0.008). Additionally, the difference between their mean scores on both PRAQ-R2 and its subscales of fear of giving birth and worries of bearing a physically or mentally handicapped child was statistically significant (p<0.05), where those in the experiment group had lower anxiety, fear of giving birth and worries of bearing a physically or mentally handicapped child. Conclusion: The tele-education offered to the pregnant women for pregnancy and birth planning during COVID-19 decreased their prenatal distress and pregnancy-related anxiety.
Keywords: Covid-19; Prenatal distress; Pregnancy-related anxiety; Tele-education